Hubungan Kondisi Lingkungan dengan Keberadaan Jentik Aedes aegypti di Daerah Endemis DBD di Kota Banjarbaru - Norsita Agustina; Abdullah Abdullah; Edy Arianto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Banjarbaru City is one of dengue endemic area, perticularly Guntung Manggis Village. In 2018, as many as 10 people affected by DHF with the death of 2 people. The purpose of the study was to analyze the environmental conditions related to the existence of Ae. aegypti larvae. The study uses analytic studies with cross-sectional approach conducted in January 2019. The population is all houses in RT 46 RW III Banjarbaru City as many as 168 sample houses, and 63 houses using random sampling techniques. Larva data collection was carried out with the single larva method. Data on environmental conditions were obtained by measuring the degree of acidity (pH) and measurement of water temperature. Data analysis used chi-square test and fisher exact test with significance value (α) 0.05. The results showed that water temperature and type of containers were related to the presence of Ae . aegypti larvae (p-value 0.000). While the degree of acidity (pH) is not related to the presence of Ae. aegypti larvae. (p-value 0.144).